IDENTIFIKASI JENIS BAMBU YANG DIMANFAATKAN DI HUTAN TEMBAWANG DUSUN TEKALONG DESA SETIA JAYA KECAMATAN TERIAK KABUPATEN BENGKAYANG - Tika, Katarina; Herawatiningsih, Ratna; Sisillia, Lolyta (Universitas Tanjungpura, 2020)
Bamboo has been known by people for generations and has good properties to be used. The purpose of this study was to identificated types of bamboo that grow in Tembawang Forest of Tekalong and obtain data on the utilization of bamboo carried out by the people of Tekalong, Â Setia Jaya Village, Teriak District, Bengkayang Regency. The method used in this study is a survey method. Data collection techniques, with observation and interviews using the help of a questionnaire. Sampling at the research location was done by purposive. The sampling technique for bamboo at the study site was using double plots measuring 5 mx 5 m.The amount of bamboo found in 4 areas of Tembawang Forest in Tekalong are 6 types of 3 different genera namely the genus Schizostachyum, Gigantochloa and Bambusa. The types of bamboo include: kayan (Schizostachyum flexuosum Widjaja), gare (Schizostachyum brachycladum Kurz), tarenk (Gigantochloa hasskarliana (Kurz) Backer ex Heyne), bangking (Gigantochloa balui K.M. Wong), betung (Gigantochloa levis (Blanco) Merr.), aur (Bambusa vulgaris Schrad ex Wendl). Bamboo in Tekalong can be used as raw material for making handicrafts, traditional ceremonies, making lemang, consumed and other benefits.Keywords :Identification, Bamboo, Utilization, Tembawang Forest